Salivary HPV Persistence Following Treatment of Oropharyngeal Squamous Cell Carcinoma. (October 2022) - Quimby, Alexandra E.; Lagiou, Pagona; Purgina, Bibiana; Corsten, Martin; Johnson-Obaseki, Stephanie
Objective: To determine the persistence of human papillomavirus (HPV) infection following treatment of HPV-positive oropharyngeal squamous cell carcinoma (HPV + OPSCC). Methods: A cross-sectional study was undertaken at The Ottawa Hospital (Ottawa, ON, Canada), a tertiary academic hospital and regional cancer center. Adult patients who were diagnosed with HPV + OPSCC between the years of 2014 and 2016 and treated with curative intent, and who were alive and willing to consent were eligible for inclusion. A saliva assay was used to test for the presence of HPV DNA in a random sample of patients. qPCR was used to amplify DNA from saliva samples. Results: Saliva samples were obtained from 69 patients previously treated with HPV + OPSCC. All patients had a minimum of 2 years of follow-up. 5 patients tested positive for HPV: 2 were positive for HPV-16, 2 for HPV-18, and 1 "other" HPV type. No patient in our study cohort had suffered recurrence post-treatment. Conclusions: This study is the first to demonstrate the prevalence of persistent oncogenic HPV DNA in saliva following treatment for HPV + OPSCC. This prevalence appears to be low, despite the fact that persistent HPV infection is a precursor for the development of HPV + OPSCC. This finding raises questions about what factors influence the clearance or persistence of HPV DNA in saliva after treatment for HPV + OPSCC, and may add to our understanding about the longitudinal effects of HPV infection in these cancers.